Advances in sequence stratigraphy - Montenari, Michael, 1971- (Stratigraphy & timescales (Series), 2017)
Advances in Sequence Stratigraphy, Volume Two covers current research across a wide range of stratigraphic disciplines, providing information on the most recent developments for the geoscientific research community. This fully commissioned review publication aims to foster and convey progress in stratigraphy, including geochronology, magnetostratigraphy, lithostratigraphy, event-stratigraphy, isotope stratigraphy, astrochronology, climatostratigraphy, seismic stratigraphy, biostratigraphy, ice core chronology, cyclostratigraphy, palaeoceanography, sequence stratigraphy, and more. Contains contributions from leading authorities in the field Informs and updates on all the latest developments in the field. Aims to foster and convey progress in stratigraphy, including geochronology, magnetostratigraphy, lithostratigraphy, event-stratigraphy, and more.